3-Butadienyl-β-lactams: A useful synthon for functionalized heterocycles. Issue 24 (16th December 2020) - Bhargava, Gaurav; Mann, Maninderjeet K.; Naikoo, Rayees Ahmad
Abstract: 3-Butadienyl- β -lactams are useful organic synthon which have efficiently been explored for the synthesis of a variety of heterocyclic systems. The present review compiles the various reports on the synthesis of 3-butadienyl- β -lactams and their explorations in the development of variety of monocyclic as well as condensed heterocyclic systems. Graphical Abstract: